2009
DOI: 10.1177/0898264309332838
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving Tasks and Training Interest of Family Caregivers of Medically Ill Homebound Older Adults

Abstract: Objectives This study assessed the caregiving activities and training interests of family caregivers of medically ill older adults without dementia who receive home health care. Methods Participants were 101 family caregivers of patients from the Training in the Assessment of Depression (TRIAD) study. Caregivers were assessed using a sociodemographic questionnaire and measures of caregiver tasks and training interest. Results Family caregivers provided a variety of caregiving tasks and their interest in tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 29 publications
(31 reference statements)
4
16
0
Order By: Relevance
“…They also requested training in basic nursing and information about dementia and stroke. Similar findings were reported by five other studies (Landmark et al., ; McCormack & Skatvedt, ; Ploeg, Biehler, Willison, Hutchison, & Blythe, ; Saunders, ; Wilkins, Bruce, & Sirey, ). The key message in these studies was that the care partners needed knowledge about their care receivers' diseases, as well as practical skills to take care of themselves.…”
Section: Resultssupporting
confidence: 90%
“…They also requested training in basic nursing and information about dementia and stroke. Similar findings were reported by five other studies (Landmark et al., ; McCormack & Skatvedt, ; Ploeg, Biehler, Willison, Hutchison, & Blythe, ; Saunders, ; Wilkins, Bruce, & Sirey, ). The key message in these studies was that the care partners needed knowledge about their care receivers' diseases, as well as practical skills to take care of themselves.…”
Section: Resultssupporting
confidence: 90%
“…A survey of the family caregivers of older home healthcare patients found that family members already provided a variety of relevant caregiver tasks but were also interested in receiving training in improve and extend those skills. [89] This interest in training was independent of the nature and extent of tasks they currently provided to their family member. Black caregivers expressed greater overall interest in receiving training than did white caregivers, as did younger caregivers compared to same-generation caregivers.…”
Section: Depression Care Management In Home Healthcare; the Depressiomentioning
confidence: 99%
“…Depression adds to personal suffering, family burden, and risk of hospitalization, falls, and other poor outcomes. 57,44 Among patients with clinically significant depression, the CAREPATH intervention was associated with a 5.6 point decline in HDRS, indicating meaningful changes in depression severity (e.g., from moderate to mild; mild to minimal) and consistent with interventions in primary care. 21 Effect sizes at 6 and 12 months (Cohen’s d: 0.32 and 0.49 respectively) were also consistent with primary care studies 4548 and considered beneficial by the Community Preventive Service Task Force.…”
Section: Discussionmentioning
confidence: 89%